PERSONALITY-ORIENTED APPROACH TO STUDY: PROS AND CONS - ANIKIN, IGOR; LAPTEVA, SVETLANA; KOZLOV, ANATOLIY (The journal of contemporary issues in business and government, 2021)
Background: New trends in the educational sector development are caused by the transformation of the society's socio-economic structure and by values changing. New tendency and pandemic conditions especially require more lability. It gives and more possibilities and more problems at the same time. Materials and Methods: It have been noted individual learning forms are not strange for most people. We have learned the pros and cons of the individual learning systems in front of both teacher and student. Results: The construction of the individual educational system is an urgent task of modern education. The development of information and communication technologies that took place at the end of the previous century has triggered global alterations, and the new interpretation of educational processes too. The individual approach is the most effective realization of the competency model because of its centered around each individual with his singularities. The article proposes to analyze the advantages and disadvantages of the individual approach through the scheme: analysis of its base, components, and formulation of different tasks for each student. Discussions and Conclusions: Our outcomes demonstrate there is no single right, any learning form has its pros and cons. It depends on the learning direction, learning stimuli of the student, and teacher's proper to be in lability and new tendency.